2018
DOI: 10.25258/phyto.v9i07.11165
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Antioxidant and Antimicrobial Activity of Carrot Peel

Abstract: The objectives of the study were to assess the total phenolic content and flavonoid content, and to investigate the antioxidant and antimicrobial potential of carrot peel extracted with methanol and acetone. Total Phenolic content and Flavonoid content was higher in carrot peel acetone extract (AE) i.e. 106.36 µg/mg of GAE and 27.83 µg/mg of QE respectively than methanol extract (ME). Carrot peel acetone extract showed greater antioxidant capacity for DPPH radical scavenging activity whereas methanol extract s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
2
4
0
1
Order By: Relevance
“…In the acetone extract of lemon peels, phenols, terpenoids, saponins, and alkaloids were discovered, while the ethanol extract of lemon peels contained flavonoids, phenols, and saponins. The ethanol extract's phytochemical composition of the flavonoids, saponins and alkanoids was similar to that reported John, S. et al,. by 2017), however cardiac glycosides, diterpene, phytosterols were not found but tannin, glycosides, carbohydrate, proteins were not found were similar to reported by John et al, 2017.…”
Section: Resultssupporting
confidence: 85%
“…In the acetone extract of lemon peels, phenols, terpenoids, saponins, and alkaloids were discovered, while the ethanol extract of lemon peels contained flavonoids, phenols, and saponins. The ethanol extract's phytochemical composition of the flavonoids, saponins and alkanoids was similar to that reported John, S. et al,. by 2017), however cardiac glycosides, diterpene, phytosterols were not found but tannin, glycosides, carbohydrate, proteins were not found were similar to reported by John et al, 2017.…”
Section: Resultssupporting
confidence: 85%
“…Phenolic compounds give antioxidant activity as free radicals terminator and metal chelator, preventing autoxidation from occurring (Shahidi et al, 1992). Meanwhile, lavonoid compounds show antioxidant activity as a free radical scavenger and metal ion chelation to inhibit lipid peroxidation (John et al, 2018;Pourmorad et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Henderson et al [31] highlighted the antibacterial properties of a lemon peel extract against Escherichia coli., Staphylococcus aureus, Salmonella enteritidis, and Listeria monocytogenes. Jonh et al [32] also reported that employing different solvents during the extraction process might result in extracts with varying antimicrobial capacity, showing the impact of the extraction method on the antimicrobial effectiveness of the extract. For instance, the authors demonstrated that the methanolic extract showed higher activity against S. flexneri, S. aureus, and E. coli, while the acetone extract was only effective against S. aureus and E. coli, and the ethanolic extract presented higher antimicrobial capacity against P. aeruginosa and S. enterica serovar Typhimurium.…”
Section: Lemon Peel Extract Antimicrobial Activitymentioning
confidence: 99%